European Union Policy in the South Caucasus after the Karabakh War of 2020 - K. V. Yumatov (Вестник Кемеровского государственного университета, 2022)
The article focuses on the transformation of the European Union’s policy in the South Caucasus after the NagornoKarabakh war of 2020. Before the war, the foreign and security policy in the region had depended on the OSCE Minsk Group, Georgia’s role in the Russian-Georgian confrontation, and the Eastern Partnership program for the South Caucasus. After Azerbaijan won the Nagorno-Karabakh war with Turkey’s support, the previous line of policy stopped being effective. It failed to unite the countries of the South Caucasus, to remove the Russian Federation from the region, and to make the European Union a real mediator in the conflict zone. The democratization of the local political regimes also failed, despite the proEuropean position of Georgia and the velvet revolution in Armenia. As a result of the Armenian-Azerbaijani war of 2020, Russian and Turkish troops entered the South Caucasus, and Russia, Turkey, and Iran started acting as peace mediators. The European Union failed to strengthen the role of the OSCE Minsk Group and the mechanisms of the Eastern Partnership in the region. Ever since 2020, it has been trying to develop a common policy for all ethnic and inter-confessional conflicts in the postSoviet space. The European Union keeps failing in its competition and partnership with Russia, while Turkey is getting more active and independent in the region. Thus, the European Union will have to develop a new model of influence in the South Caucasus and the whole post-Soviet space. In the current global confrontation, it is very important to find an international actor able and willing to interact with all parties. The European Union seems to be the one, and its actions in resolving regional conflicts require a detailed research.